2021
DOI: 10.54055/ejtr.v27i.2125
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Serbian tourists' risk perception on their travel intentions during the COVID-19 pandemic

Abstract: The purpose of this study is to examine the impact of Serbian tourists’ risk perception on their intentions to travel during the COVID-19 pandemic with the control of socio-demographic characteristics. This research was conducted in the period from 18 May until 24 May 2020, on a sample of 348 respondents, through an online questionnaire. The principal component analysis identified five categories of the perceived risk affecting travel intentions during the COVID-19 pandemic: the health risk, the psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 74 publications
8
51
0
4
Order By: Relevance
“…In turn, this could have had an impact on participants’ aesthetic and tourist intention responses. Alternatively, it might be the case that negative influence of the COVID-19 on a potential tourist's perceived risk might have decreased their intention to travel during the pandemic (see for e.g., the studies of Xie et al, 2021, and Jin et al, 2021, on Chinese travelers; Pappas, 2021, and Pappas and Glyptou, 2021, on adult residents of Athens; and Perić et al, 2021, on Serbian travellers). Further research is suggested to expand the scope of our investigation by examining the moderating effect of participants’ experience linked to COVID-19 in aesthetic and tourist judgements in the formation of tourist destination images.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this could have had an impact on participants’ aesthetic and tourist intention responses. Alternatively, it might be the case that negative influence of the COVID-19 on a potential tourist's perceived risk might have decreased their intention to travel during the pandemic (see for e.g., the studies of Xie et al, 2021, and Jin et al, 2021, on Chinese travelers; Pappas, 2021, and Pappas and Glyptou, 2021, on adult residents of Athens; and Perić et al, 2021, on Serbian travellers). Further research is suggested to expand the scope of our investigation by examining the moderating effect of participants’ experience linked to COVID-19 in aesthetic and tourist judgements in the formation of tourist destination images.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect is that almost all studies confirmed the expected preferences to domestic tourism vs. traveling abroad in the time of pandemic. Yet, Perić et al (2021) disclosed that -in the case of Serbia -an increase in health risk assessment increased the chance of traveling abroad, meaning that Serbians perceived the health risk as being lower abroad than in their home country. Thus, the 'home-is-safer-than-abroad' bias outlined by Das & Tiwari (2020) has also been challenged in a specific country context.…”
Section: Literature Review 21 Confirmed Expectations and Unexpected R...mentioning
confidence: 99%
“…The demand-side focus was first ensured by desktop research based on previous crisesrelated experience (Peters, Peters & Peters, 2020;Zenker & Kock, 2020;Wen, Kozak, Yang and Liu, 2020;Matiza, 2020), followed by what Rogerson & Rogerson (2021) called 'an avalanche' of empirical studies undertaken in different countries to understand COVID-19 induced travel intentions and preferences. Some authors considered that the tourism industry recovery would all depend on the mindset of tourists (Wachyuni & Kusumaningrum, 2020) while many others highlighted a variety of factors influencing risk perceptions and travel decision making: psychographic and demographic characteristics, cultural background, knowledge, past travel experience, fear of contraction, media coverage, and public opinions (Neuburger & Egger, 2020;Bae & Chang, 2020;Das & Tiwari, 2020;Perić, Dramićanin, and Conić, 2021;Peluso & Pichierri, 2021;Li & Ito, 2021;Golets, Farias, Pilati, and Costa, 2021;Bhati, Mohammadi, Agarwal, Kamble & Donough-Tan, 2021). Relatively less attention has been paid on the economic and political factors determining customer decisions and preferences, with some empirical studies outlining income, severity of measures against the spread of infection, trust in the health system or distrust in the risk of contamination as significant predictors of the willingness to travel (Boto-Garcia & Leoni, 2021;Perić et al, 2021;Terziyska & Dogramadjieva, 2021;Godovykh, Pizam and Bahja, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tourists always consider specific safety measures while traveling, such as avoiding walking in remote areas, having an awareness of the environment, etc. During COVID-19 pandemic, tourists have become more conscious of adopting precautionary measures ( Godovykh et al, 2021 ; Perić et al, 2021 ). For tourists, the experience of good safety measures plays a very important role in building trust.…”
Section: Introductionmentioning
confidence: 99%